2007
DOI: 10.1016/j.ijlp.2007.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Workers describe the effect of the workers' compensation process on their health: A Québec study

Abstract: This article reports on a Canadian qualitative study designed to examine the workers' experience of the workers' compensation process and to look at the effects of the process on the physical and mental health of claimants. Eighty five in depth individual interviews of injured workers in Québec and six group interviews with workers and worker advocates from Québec, Ontario and British Columbia were analysed to determine the positive and negative impact on claimant health of various steps of the workers' compen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
151
0
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 167 publications
(174 citation statements)
references
References 33 publications
13
151
0
10
Order By: Relevance
“…Studies in Canada [Ison, 1986;Lippel, 1999;Beardwood et al, 2005;Eakin, 2005;Lippel, 2007;MacEachen et al, 2007aMacEachen et al, , 2010, Australia [Roberts-Yates, 2003;Sager and James, 2005], and the United States [Lax and Manetti, 2001;Strunin and Boden, 2004] have shown that many workers' compensation claimants report feeling stigmatized by the process, blamed for being an injured worker, and shunned by the community and healthcare professionals because of their status as an injured worker.…”
Section: Discourses Underpinning Workers' Compensation Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies in Canada [Ison, 1986;Lippel, 1999;Beardwood et al, 2005;Eakin, 2005;Lippel, 2007;MacEachen et al, 2007aMacEachen et al, , 2010, Australia [Roberts-Yates, 2003;Sager and James, 2005], and the United States [Lax and Manetti, 2001;Strunin and Boden, 2004] have shown that many workers' compensation claimants report feeling stigmatized by the process, blamed for being an injured worker, and shunned by the community and healthcare professionals because of their status as an injured worker.…”
Section: Discourses Underpinning Workers' Compensation Systemsmentioning
confidence: 99%
“…The adversarial nature of a system is thought to increase in systems that are highly experience rated [Ison, 1998;Pransky et al, 1999;Lippel, 2007;Quinlan et al, 2010]. Although appeals are only a small part of the adversarial process, an increase in appeals over the years can provide an indicator of the increasing adversarial nature of the system.…”
Section: Discourses Underpinning Workers' Compensation Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The worker is subject to the power imbalance with the system, prolonged claims and appeals processes, medical reports being used out of context, and a general lack of knowledge about rights. Claims can be manipulated by ignoring or contesting diagnoses, using confusing jargon and legalistic communication, slow payments to non-preferred physician to discourage treatment [39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Underreporting Of Msdsmentioning
confidence: 99%